2007
DOI: 10.2217/17460875.2.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol Metabolism In Adipose Tissue

Abstract: Triacylglycerol (TAG) in adipose tissue serves as the major energy storage form in higher eukaryotes. Obesity, resulting from excess white adipose tissue, has increased dramatically in recent years resulting in a serious public health problem. Understanding of adipocyte-specific TAG synthesis and hydrolysis is critical to the development of strategies to treat and prevent obesity and its closely associated diseases, for example, Type 2 diabetes, hypertension and atherosclerosis. In this review, we present an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
125
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(133 citation statements)
references
References 86 publications
1
125
0
Order By: Relevance
“…Indeed, the unique and canonical function of adipocyte is to store triglyceride and to release fatty acids for other tissues and organs (33). Here, we found that lipids were transferred from the isolated adipocytes to melanoma cells in a co-culture system.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, the unique and canonical function of adipocyte is to store triglyceride and to release fatty acids for other tissues and organs (33). Here, we found that lipids were transferred from the isolated adipocytes to melanoma cells in a co-culture system.…”
Section: Discussionmentioning
confidence: 83%
“…Lipolysis for the provisions of fatty acids as a fuel for other tissues is a unique function of adipose. 10 However, chronically elevated circulating levels of fatty acids, commonly observed in obesity, are associated with negative metabolic consequences such as ectoptic lipid deposition and insulin resistance. 29 Our results may suggest that over-accumulation of Ab in adipose tissues might promote lipolysis, which could increase availability of fatty acids and glycerol and contribute to lipotoxicity in other organs.…”
Section: Discussionmentioning
confidence: 99%
“…2 Various Ab isoforms can be generated from cleavage in the Ab N-terminus such as Ab 3-40/42 , Ab 11-40/42 and Ab 17-40/42 . Alternative peptides can be derived from cleavage at the C-terminus including Ab , Ab , Ab and Ab [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . Ab [25][26][27][28][29][30][31][32][33][34][35] is derived from cleavage at both termini, and is considered the core functional domain of Ab peptides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This statement supported by Fantuzzi and Mazzone (2007), stating that the higher rat intake, the amount of excess energy will be higher, so it will be deposited in TAG form in adipose tissue that contributes in WAT enlargement. However, in energy deficiency TAG in adipose tissue will be broken down into fatty acid that will be used as energy source by another organ [14]. It can be concluded that adipose cell enlargement results from imbalanced lipogenesis and lipolysis [15].…”
Section: Plasma Lipid and Body Fat Massmentioning
confidence: 99%